Molecular characterization and tissue tropism of an Iraqi field isolate of fowl adenovirus serotype 8a in broiler chickens - Mohammed Abdullah Hamad; Ahmed J. Alfahdawi; Basim Mohamed Manswr (PLoS ONE, 2026)
Background Inclusion body hepatitis is still a threat to broiler farms and recent findings indicate that FAdV-8a is re-emerging in several areas. Limited data are available on circulating strains in the Middle East. The objectives of this work were to characterize an Iraqi field isolate and to study its effect on various tissues in experimentally infected broilers. Methods The experiment was conducted on a total of 95 Cobb-500 chicks that were randomly assigned into infected and control groups. At 14 days of age, the chicks were inoculated with the isolate ocularly. Birds were necropsied 21 days post-infection, with organ weights, gross and histopathological findings, and qPCR data targeting the hexon gene used to assess the infection. Results Infected birds had increased liver and spleen sizes indicated by an increase in the organ/body weight ratio. The liver was pale and swollen, spleens were increased in size and dark, the superficial area of the kidney presented a diffuse pallor while the changes in the heart were negligible. Microscopically, there were severe hepatic degeneration and necrosis, noticeable splenic lymphoid depletion, and tubular injury in the kidneys consistent with secondary changes, with mild cardiac alterations. These results were further confirmed by qPCR analysis, which demonstrated relatively high viral genome copies in liver and moderate copies in spleen, whereas minimal copy numbers were found in heart. Conclusion The hepatic involvement was the predominant disease picture induced in chickens by the Iraqi FAdV-8a isolate, with associated splenic changes and mild renal histological alterations and slight cardiac involvement. The infection was non-fatal to the controlled animals, indicating low virulence. These results provide important regional information that can help direct monitoring and serotype-specific prevention strategies.